Test to Measure the Attitude of Horse Stakeholders Towards Horse Keeping - Raj J., Ana; Makarabbi, Gururaj; Dedar, R. K.; Pal, Yash (Indian Journal of Extension Education, 2022)
A scale was constructed and standardized to measure the attitude of horse keepers towards horse management using Thurstone’s “equal-appearing interval” method from March 2021 to September 2021. Several attitude statements concerning the psychological object i.e., horse management were collected. 36 experts responded unbiasedly to the 22 attitude statements. On the basis of scale values and Q-values, only 8 statements were incorporated in the final attitude scale. When administered in a non-sample area, the reliability coefficient of the whole test was 0.88 in Spearman-Brown formula. The content validity was computed using index of reliability formula and it was 0.93. When the constructed attitude scale was administered among 60 horse stakeholders (horse keepers, veterinarians and NGOs) from October 2021 to April 2022, majority (66%) of the respondents had unfavourable attitude towards horse keeping which is evident from the declining horse population in India. The developed attitude scale can be applied practically for identifying the attitude of horse keepers which will aid policy-makers in right decision-making.
Keywords: Attitude; Horse management; Population decline; Field veterinarians; Thurstone’s scale